Cartography of a Blind Spot: An Exploratory Analysis of European Border Cities. (September 2017) - Sohn, Christophe
Abstract: Despite the importance of national borders in the process of European integration and its destiny, border areas remain relatively misrecognised. This is particularly true as regards the contemporary geography of border cities across Europe. It is therefore difficult to assess what importance border cities and cross‐border urban regions have and how they have evolved in parallel with the transformation of European borders. The aim of this paper is to highlight the urban dimension of border regions in Europe and, in particular, the diversity of configurations present. Through an original cartography of border cities, we hope to draw the attention of the research community interested in borders and border regions to an unfamiliar aspect of European borderlands and some of the issues and questions it raises.